2001
DOI: 10.1007/s00248-001-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Enterobacter Genotypes in Sediments and the Underlying Hyporheic Zone of an Agricultural Stream

Abstract: Population studies of enteric bacteria in an agriculturally impacted stream (Ledbetter Creek, Murray, Kentucky, USA) were conducted over a period of 2 years. Total number of bacteria, cultivated heterotrophic aerobic bacteria, and enteric bacteria showed significant differences between winter and summer. The cultivated numbers of heterotrophic aerobic bacteria and enteric bacteria were significantly more abundant in summer than in winter. The abundance of enteric bacteria was 12.9% in an upwelling zone and 9.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Seasonal variation in microbial communities has been documented in numerous terrestrial (25,38,63,65) and aquatic (5,8,20,36,44,55,66) environments, and we have previously shown that hyporheic microbial communities inhabiting streams of the western Rocky Mountains not impacted by mining exhibit seasonal patterns in diversity, abundance, and activity, which peaks during the fall (24,33).…”
mentioning
confidence: 71%
“…Seasonal variation in microbial communities has been documented in numerous terrestrial (25,38,63,65) and aquatic (5,8,20,36,44,55,66) environments, and we have previously shown that hyporheic microbial communities inhabiting streams of the western Rocky Mountains not impacted by mining exhibit seasonal patterns in diversity, abundance, and activity, which peaks during the fall (24,33).…”
mentioning
confidence: 71%
“…However, environmental gradients can include factors that covary with the contaminant, thereby complicating analysis of results (52). Factors that influence aquatic microbial community structure include dissolved nutrient levels (8,23,35,49), carbon quality and quantity (53), flow rates and sediment porosity (33,77), pH (23), viral lysis (65,71), and grazing (36,40,65,70). These and other potential covariates were controlled for in the present experiment through the experimental design, in which microbial community inoculum, water chemistry, total carbon, temperature, and other environmental parameters were held constant while the degree of contamination with the metal mixture was adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its clinical significance, E. cloacae plays an important role as a pathogen in plants (2,34) and insects (15) and is ubiquitous in the terrestrial and aquatic environments (22). This diversity of habitats is mirrored by the genetic variety of the nomenspecies E. cloacae, which has been demonstrated in several studies by biotyping and serotyping (16,47), ribotyping and phage typing (46), pulsed-field gel electrophoresis and enterobacterial repetitive intergenic consensus PCR (ERIC-PCR) (18), and internal transcribed spacer-PCR and random amplification of polymorphic DNA (RAPD)-PCR (6).…”
mentioning
confidence: 99%